The Slaughtering and Dressing Procedures of Livestock Inside the Butcher Shops Generate High Levels of Bacterial Contamination - Fawzi I. Irshaid,; Jacob H. Jacob ,; Saifaldeen I. Alhawamdeh, (Journal of Basic & Applied Sciences, 2018)
Background and Objective: Raw meats from animal carcasses are most frequently contaminated with bacteria during the slaughtering and dressing process. Therefore, this study aimed to determine the bacterial quality of raw meat from lamb, goat and beef carcasses immediately after slaughtering at butcher shops in Al-Mafraq city-Jordan. Materials and Methods: A total of 243 meat samples were aseptically cut from the hand, leg and back of carcasses at three butcher locations, designated as site-C (the central part of the city), site-N (the north side of the city) and site-S (the south side of the city). Samples were processed and then cultured on nutrient agar and xylose lysine deoxycholate (XLD) agar plates aerobically at 35 °C for 48 h for enumeration of bacteria and total Enterobacteriaceae count (TEC) by aerobic plate count (APC). APC and TEC were expressed as colony forming units per gram of meat (CFU/g). Results: APC and TEC in the raw meats ranged from 11.6-28.1 X 106 CFU/g on nutrient agar and from 23-120 X 103 CFU/g on XLD agar medium. By meat type, the lamb had the highest APC and TEC, followed by beef. By location, the highest APC and TEC were shown in the C-Site, followed by the S-Site. There were significant differences between APC counts by location and meat type (P<0.05). APC and TEC at the legs of the tested carcasses were significantly higher than the hand and back regions (P < 0.05). Conclusion: There were high levels of bacterial loads on raw meat carcasses during slaughtering and dressing process inside the butcher shops. The bacterial load exceeded the guideline set up by international studies and was influenced by location, meat type and part of the carcass. To improve the quality of locally produced raw meat, these findings emphasized the need to curb slaughtering animal inside the butcher shops.